Rhetoric and Literature in the Classical Arabic Tradition: From Stylistic Devices to the Literary Genres - Hasyim Ashari; Andi Abdul Hamzah (Al-Uslub: Journal of Arabic Linguistic and Literature, 2025)
This research highlights the position of rhetoric in the classical Arabic tradition, as well as several literary genres that developed during that period,particularly those with unique characteristics that distinguish them from the literature of other nations. The aim is to explain how the Arab people paid great attention to the importance of beauty and effectiveness in language to strengthen the message conveyed to the listener. In addition, this study also aims to explore the characteristics and uniqueness of several literary genres such asal-qas}i>dah, al-khamriyyah, al-maqa>mah, dan al-ams|a>l. This research uses a descriptive qualitative approach with a text analysis method where data is taken from various references, especially those related to classical Arabic literature. The findings are as follows: 1) The Arabs have long emphasized the aspects of beauty and effectiveness in speech, even before rhetoric (al-balagha) became a formal academic discipline. 2) In the classical Arab tradition, there are several literary genres that are unique and distinct from those of other cultures, reflecting the creativity of Arab writers at that time.